The Moho reflectivity of the subduction beneath the Southwestern Alps from ambient seismic noise autocorrelations. Issue 1 (23rd February 2022) - Ashruf, T N; Morelli, A
SUMMARY: The Western Alps shows a complex crustal organization due to the subduction of the European Plate beneath the Adriatic Plate and exhumation of the mantle wedge. The lithospheric structure of the Western Alps, that may hold significance for understanding orogenic processes and evolution, has been the subject of many geophysical studies, but the Moho profile remains unclear and this has led to controversies about the depth and extent of the European Plate beneath the Adriatic Plate. With the goal of retrieving detailed information on crustal constitution, we use autocorrelation of seismic ambient noise as a tool to map the body wave reflectivity structure at the subduction zone under the southwestern Alps. We use data recorded by the China–Italy–France Alps (CIFALPS) seismic transect, that includes 45 stations located approximately 5–10 km apart along a profile crossing the Alpine continental subduction in the Western Alps. We analyse the data set in four different frequency bands between 0.09 and 2 Hz. We automatically pick the arrival time of the Moho reflection in the second derivative of the envelope of the autocorrelation stack using prior Moho information. The 0.5–1 Hz frequency band mostly gives the best result due to the clear changes in reflectivity along the waveforms of the autocorrelation stacks after the picked arrival times of the Moho reflections. We find spatial coherence between 18 and 23 km depth in the western portion of the profile, indicating relatively homogeneous crustal rocks, and highly reflective structure under the central mountain range, due to the existence of a highly faulted zone. The very thin crust and the underlying mantle wedge known as the Ivrea body show instead high transparency to seismic waves and absence of reflections. The subduction profile of the European Plate shows a steep trend as compared to previous studies. We discuss autocorrelation stacks and Moho depths obtained from the arrival times of the picked reflectivity change in comparison with previous studies to validate the different reflection structures. Stacked ambient noise autocorrelations reliably image varied crustal properties and reflectivity structures in the highly heterogeneous region of the southwestern Alps.